Maritime trade and biological invasions management: a seaport platform of environmental surveillance in Cotonou, Benin, as a pilot multi-stakeholder initiative - Adamjy, T.; Tchabi, A.; Gauthier, P.; Houemenou, G.; Goergen, G .; Gouriveau, F.; Badou, S.; Dossou, H.; Etougbetche, J.; Lokossou, A. S.; Missihoun, A. A.*; Kindomissi, M.; et al. (2024)
In the context of increasingly visible consequences of global changes, claims for science-guided concrete recommendations towards decision makers and socio-economic stakeholders are multiplying. This requires that science production keeps aligned with societal needs and constraints, and that dialog and interactions between academics and non-academics remain possible and constructive, leading to mutual understanding and, in fine, operational collaboration. Though theoretically sound, this is not always straightforward and easy to implement in the real life. We here share what we feel is a successful story where scientific production, societal obligations and socio-economic stakeholders’ objectives meet and fuel collaborative action. In essence, we describe and analyze the process that led to the setup of the Seaport Platform of Environmental Surveillance (PPSE, or Plateforme Portuaire de Surveillance Environnementale in French) in 2021 in Cotonou, Benin, the first lab device housed within an international seaport, conducted by academics and dedicated to invasive species monitoring and management. The first part of our paper provides a general overview of the background, namely the scientific and regulatory aspects of biological invasions, as well the local context of Cotonou Seaport (CS). The second part focuses on the origin and co-construction process of the PPSE. We then conclude by discussing some of the identified issues that should be addressed to reach autonomy and sustainability.